Heterostructured electrode with concentration gradient shell for highly efficient oxygen reduction at low temperature - Zhou, W.; Liang, F.; Shao, Zongping; Chen, J.; Zhu, Z. (2011)
Heterostructures of oxides have been widely investigated in optical, catalytic and electrochemical applications, because the heterostructured interfaces exhibit pronouncedly different transport, charge, and reactivity characteristics compared to the bulk of the oxides. Here we fabricated a three-dimensional (3D) heterostructured electrode with a concentration gradient shell. The concentration gradient shell with the composition of Ba 0.5-x Sr 0.5-y Co 0.8 Fe 0.2 O 3-d (BSCF-D) was prepared by simply treating porous Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-d (BSCF) backbone with microwave-plasma. Electrochemical impedance spectroscopy reveals that the oxygen surface exchange rate of the BSCF-D is enhanced by ~250% that of the pristine BSCF due to the appearance of the shell. The heterostructured electrode shows an interfacial resistance as low as 0.148 O cm 2 at 550°C and an unchanged electrochemical performance after heating treatment for 200 h. This method offers potential to prepare heterostructured oxides not only for electrochemical devices but also for many other applications that use ceramic materials.